PERBANDINGAN TEGANGAN LISTRIK YANG DIHASILKAN BUAH PEDADA (SONNERATIA CASEOLARIS) UTUH DENGAN BUAH YANG DIBELAH - Thea Deninta (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2020)
A research has been conducted which aims to find out how to increase the amount of electric voltage produced by pedada fruit (Sonneratia Caseolaris) with a fixed number of fruits. In this study using an experimental method by connecting copper electrodes (Cu) as a cathode and iron (Fe) as an anode. The fruit used is fruit pedada (Sonneratia Caseolaris) intact and divided. In measuring the strength of the current and voltage connected to the Multimeter with Cu and Fe electrodes as the link. The results showed that the current strength and voltage delivered by 7 whole pieces, namely for the number of 1 pedada is (0.1 mA; 0.53 V), for 2 pieces (0.11 mA; 1.09 V), for 3 pieces (0.13 mA; 1.4 V), for 4 pieces (0.13 mA; 1.75 V), for 5 pieces (0.14 mA; 2.5 V), for 6 pieces (0, 13 mA, 2.9 V) and for 7 units (0.15 mA; 3.2 V); and 7 parts divided by a quarter, namely for the number of parts a quarter of pedada fruit 1 part is (0.13 mA; 0.53 V), for 2 parts (0.15 mA; 1.03 V), for 3 parts (0.1 mA; 1.52 V), for 4 parts (0.13 mA; 2.05 V), for 5 parts (0.14 mA; 2.63 V), for 6 parts (0.13 mA; 3.27 V) and for 7 units (0.1 mA; 3.78 V). The voltage delivered by a quarter fruit is the same as a whole fruit, so it can be concluded that the fruit being cleaved is more effective in its use because it delivers the same voltage as a whole fruit.